A high-contrast polymorphic difluoroboron luminogen with efficient RTP and TADF emissions. Issue 10 (17th January 2023) - Wang, Xin; Wu, Xiaofu; Wang, Tong; Wu, Yuliang; Shu, Haiyang; Cheng, Zhiqiang; Zhao, Lei; Tian, Hongkun; Tong, Hui; Wang, Lixiang
Abstract : Three polymorphs of a N, S -chelated four-coordinated difluoroboron-based emitter display high contrast green (G), yellow (Y) and red (R) emissions with TADF character for the G- and R-Crystals, and RTP for the Y-Crystal, tuned by different molecular conformations and packings. Abstract : A simple N, S -chelated four-coordinated difluoroboron-based emitter is reported with three polymorphs, which emit high contrast green (G), yellow (Y) and red (R) light. Interestingly, the G and R-Crystals show different thermally activated delayed fluorescence (TADF) at 530 nm and 630 nm with a remarkable emission spectral shift of up to 100 nm, while the Y-Crystal exhibits room temperature phosphorescence (RTP) at around 570 nm with a high solid-state quantum yield of 77%. Single crystal analysis and theoretical calculations reveal that different molecular conformations and packing modes lead to distinct triplet exciton conversion channels.